2019
DOI: 10.1017/s1092852919001731
|View full text |Cite
|
Sign up to set email alerts
|

An overview of jail-based competency restoration

Abstract: Forensic populations in the United States are increasing, driven largely by a rise in individuals determined to be Incompetent to Stand Trial (IST). Across most states, including California, the number of mentally ill inmates awaiting competency restoration has increased dramatically in recent years. Traditionally, competency restoration has taken place in state hospitals, but incompetent inmates often experience a significant wait for state hospital beds because of the rising demand for beds in such facilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Finally, and specific to this article, critics point to the continuing lack of empirical support for the JBCT model (Danzer et al, 2019;Kirkorsky et al, 2019;Wik, 2018). Despite the proliferation of JBCT programs, the variability in its implementation across multiple states and counties has been a challenge to building a necessary evidence base, in two respects.…”
Section: Advantages and Disadvantages To Implementationmentioning
confidence: 96%
See 2 more Smart Citations
“…Finally, and specific to this article, critics point to the continuing lack of empirical support for the JBCT model (Danzer et al, 2019;Kirkorsky et al, 2019;Wik, 2018). Despite the proliferation of JBCT programs, the variability in its implementation across multiple states and counties has been a challenge to building a necessary evidence base, in two respects.…”
Section: Advantages and Disadvantages To Implementationmentioning
confidence: 96%
“…The growth of the JBCT model has been fueled by multiple perceived advantages, including accelerated access to more timely restoration and mental health services, reduction in prolonged incarceration for individuals waiting for limited hospital beds, reduction in the cost of restoration compared with hospitalization, removal of incentives for malingering, and improved proximity to local attorneys and family support (Ash et al., 2020; Danzer et al., 2019; Jennings & Bell, 2012; Kirkorsky, Gable, & Warburton, 2019; California Legislative Analyst’s Office, 2012, 2017; Rice & Jennings, 2014; Wik, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Pinals and Fuller (2020) reported that the number of forensic psychiatric beds in state hospitals is insufficient and remains a nationwide concern. Accordingly, several jurisdictions have been involved in litigation regarding delayed waiting periods ( Fuller et al, 2017 ; Kirkorsky et al, 2020 ).…”
Section: Primary Challenges Of Competency Restoration Servicesmentioning
confidence: 99%
“…In the United States, jail-based competency restoration services have emerged as a way to help address the national shortage of forensic psychiatric hospital beds (Ash et al, 2020). However, research on the efficacy of these relatively novel services is scarce, and there has been criticism that jails do not provide a sufficiently therapeutic milieu (Kirkorsky et al, 2020). In their study, the authors compared the restoration rate of justice-involved individuals at a jail-based competency restoration unit in georgia, depending on whether they received in-person services (pre-pandemic) or telehealth services (during the pandemic).…”
Section: Overview Of the Special Issuementioning
confidence: 99%